A new multi-proxy investigation of Late Quaternary palaeoenvironments along the north-western Barents Sea (Storfjorden Trough Mouth Fan) - ROMANA MELIS; KATIA CARBONARA; GIULIANA VILLA; CATERINA MORIGI; MARIA A. BARCENA; GIOVANNA GIORGETTI; ANDREA CABURLOTTO; MICHELE REBESCO and RENATA G. LUCCHI (Journal of Quaternary Science, 2018)
A new integrated micropalaeontological study on planktonic and benthic foraminifera, calcareous nannofossils and diatoms was performed on three sediment cores from the Storfjorden Trough Mouth Fan to reconstruct the Late Quaternary palaeoenvironmental and climatic history. Two main intervals were discussed: the last deglaciation (16.2–11.7 ka BP) and the Holocene. The age model relies on palaeomagnetic parameters together with 10 radiocarbon dates. Deglacial sediments had largely diluted the biogenic content which was scarce and poorly preserved. The first occurrence of Cibicidoides wuellerstorfi (benthic foraminifer), together with Turborotalita quinqueloba (planktonic foraminifer) and Coscinodiscus spp. (diatoms) at 11.3 ka BP followed the end of the Younger Dryas cold event and marked the beginning of the early Holocene warm period. Diatoms and planktonic foraminifers indicated a warming of the surface water from 10.5 to 9.2 ka BP, identifying the Holocene Thermal Maximum event. Bottom water fauna registered these warming conditions less clearly. Cooling events were identified during the Holocene, in particular the 8.2 ka BP event and the Neoglacial between 3.2 and 2 ka BP, as shown by the presence of cold-water taxa such as Gephyrocapsa muellerae (nannoplankton) and Neogloboquadrina pachyderma (planktonic foraminifer). These events were influenced by sea ice extent, cold or relatively warm current influxes.